Comparative study of a reinforced concrete frame design based on American Concrete Institute (ACI-318) and British Standards (EN 1992) - Felicien Sebahire; Theoneste Nsanzimfura; Cyprien Imanaturikumwe; Felix Hafashimana (Discover Civil Engineering)
Abstract Structural design plays an important role in providing reliable, cost-efficient, and environmentally sustainable structures. However, modern structural codes have added complexity and complication to the process. Standard codes, such as the American Concrete Institute (ACI-318) and British Standards (EN 1992), play a crucial role in the design of reinforced concrete (RC) structures. Therefore, this paper examines the results of designing an RC frame for a commercial structure using both codes, applying double note calculus to each structural member, including a panel slab, a continuous beam, a column, and a pad footing. The study completed the design at both the Ultimate Limit States (ULS) and the Serviceability Limit States (SLS) to ensure the safety and stability of the structure. ArchiCAD and LINPRO software were used, respectively in drawing and calculating the shears and moments. Thereafter, the findings showed that while the EN 1992 code takes longer to achieve the same ultimate result as the ACI-318 code, it results in a smaller sectional area for the main steel reinforcements. When used to determine the structural safety and serviceability of the designed elements, the EN 1992 code always comes up with large bending moments and axial internal loads. The same paper invites scholars and design engineers to compare and revise other codes of practice, enabling developing countries to establish their own codes.